Pharmacological Potential of Vinegar Tree Species: a study conducted by the scientific and technological prospecting techniques - Cavalcante, Katiury Castro; Pinheiro, Gladson Diniz; Pereira, Álvaro Itaúna Schalcher; Lopes Sobrinho, Oswaldo Palma; Santos, Layane Bastos dos; Ribeiro, Francisco Adelton Alves (Cadernos de Prospecção, 2019)
This research aims to describe using techniques of scientific and technological forecasting information about the vegetable species Hibiscus sabdariffa L. present on the banks of national and international data evaluating its chemical aspects and pharmacological/medical applications. For this, searches were conducted in scientific data bases Web of Science and Scopus and patent banks: National Institute of Industrial Property (INPI) and World Intellectual Property Organization (WIPO). The bases studied, Scopus and WIPO were obtained which results in more number of publications and patents filed. Nigeria was the country that published on hibiscus in the 2007-2017 period, followed by India and Taiwan. China was the country with the highest number of registered patents, holding 53% of the results. Brazil has a low proportion in the number of deposits. Documents found in the WIPO classified into sections A and C of the IPC classification, with most of them included in subclass A61K (preparations for medical, dental or hygienic purposes).